Social learning evidence gathering workshop June (Instagram photos) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
In an effort to gather the needed evidence for social learning, International Institute for Environment and Development (IIED) organised a workshop together with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in June, together with other partners, to present real-life social learning case studies from across the globe while evaluate a social learning monitoring and evaluation framework. Photos: C. Schubert (CCAFS)